VI CONGRESS WITH INTERNATIONAL PARTICIPATION «DEVELOPMENT OF PHARMACOECONOMICS AND PHARMACOEPIDEMIOLOGY IN RUSSIAN FEDERATION» (Фармакоэкономика)
VI congress with international participation «Development of pharmacoeconomicsand pharmacoepidemiology in Russian Federation», 28-29 of February, 2012, Krasnodar